Menggali Keunggulan Kompetitif UMKM, Analisis Swot dan Implikasi Strategis pada Kota Bandar Lampung - Maulana, Hikmal; Hafifah, Destri; Agustin, Amelia Putri (Journal of Economics and Management, 2024)
This study examines the concept of competitive advantage based on Michael E. Porter's theory, with a focus on its application in the local context, namely the city of Bandar Lampung. Competitive advantage is defined as the ability of an organization or region to create unique value that is able to compete in the global and domestic markets. This research explores various elements that affect the competitiveness of Bandar Lampung, including SWOT analysis, regional description, as well as supporting factors such as infrastructure, government policies, and local resources. Based on the analysis carried out, it was found that Bandar Lampung has strategic strengths, such as a supportive geographical location and potential for the creative economy, but still faces challenges such as lack of digitalization in the SME sector and environmental threats. The suggested strategic implications include economic diversification, SME digitalization, environmental conservation, and strengthening city branding. The results of this research are expected to make a real contribution to improving the competitiveness of Bandar Lampung at the national and international levels.